Thai character cluster for Braille printing characters translation - Sukhahuta R. (2014)
This paper describes how the analysis of the lexical structure of the words can be used translate from Thai writing to Braille printing characters. The context free grammar for Thai Braille is defined to recognize the structure of Thai words. The rules are defined according to Thai grammatical structure based on the word pattern consisting of consonant and vowel structure that is how they are formed to become words. The experiments showed that the translation engine can handle more complex word patterns yielding high precision of the translation results. © 2011 IEEE.